The surface composition of asteroid 162173 Ryugu from Hayabusa2 near-infrared spectroscopy - Kitazato, K; Milliken, R E; Iwata, T; Abe, M; Ohtake, M; Matsuura, S; Arai, T; Nakauchi, Y; Nakamura, T; Matsuoka, M; Senshu, H; Hirata, N; et al. (Science (American Association for the Advancement of Science), 2019)
The near-Earth asteroid 162173 Ryugu, the target of the Hayabusa2 sample-return mission, is thought to be a primitive carbonaceous object. We report reflectance spectra of Ryugu's surface acquired with the Near-Infrared Spectrometer (NIRS3) on Hayabusa2, to provide direct measurements of the surface composition and geological context for the returned samples. A weak, narrow absorption feature centered at 2.72 micrometers was detected across the entire observed surface, indicating that hydroxyl (OH)-bearing minerals are ubiquitous there. The intensity of the OH feature and low albedo are similar to thermally and/or shock-metamorphosed carbonaceous chondrite meteorites. There are few variations in the OH-band position, which is consistent with Ryugu being a compositionally homogeneous rubble-pile object generated from impact fragments of an undifferentiated aqueously altered parent body.